The Effect of Blanching Time on Antioxidant Activity and Sensory Characteristic of Brown Seaweed Sargassum sp. Tea - Ellya Sinurat; Th.Dwi Suryaningrum (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2019)
Brown seaweed Sargassum sp. is known to contain bioactive compounds needed for human. Seaweedcan be brewed into antioxidant drinks. The purpose of this study was to determine antioxidant activity andsensory properties of Sargassum sp. with variations in the duration of blanching 1, 3, and 5 minutes. Thetea was analysed for their water content, total phenols, antioxidant activity and sensory tests. The highestantioxidant activity was obtained in blanching treatment for 5 minutes with phenol content of 2.22 mg GAE/g. However, the hedonic test suggested 3 minutes blanching treatment was the best treatment to obtain theseaweed tea.